Rolling away: a novel context-dependent escape behaviour discovered in ants - Grasso, Donato A. (Sci Rep, 2020)
For animals facing dangers, the best option to optimize costs and benefits of defence sometimes may be avoidance. Here we report the discovery of a peculiar strategy adopted by Myrmecina graminicola, a cryptic ant living in forest floor. Experiments showed that when disturbed these ants respond with immobility. However, upon perceiving disturbance but under specific inclinations of the substrate, they shift to an active escaping strategy: rolling away. This is a context-dependent behaviour adopted only in appropriate circumstances. During rolling, the ants assume a ball-like shape using antennae and hind legs to obtain an active movement along a stable trajectory. Finally, we assessed the adaptive value of this strategy measuring its effectiveness in defence against enemies. This is the first example of locomotion by rolling discovered in ants and one of the very few among animals, offering opportunities for multidisciplinary research on the adaptations and biomechanics underlying it.